INNOVATIVE HOSPITALITY MODEL AS A CATALYST FOR SUSTAINABLE RURAL DEVELOPMENT - Knežević, Miroslav; Vujko, Aleksandra; Cvijanović, Drago (Economics of Agriculture, 2025)
This study explores the role of innovative hospitality models in fostering sustainable rural development through cultural integration and community engagement. Conducted in Terlan (Terlano), South Tyrol, Italy, the research surveyed 403 tourists to examine motivations related to sustainability, cultural curiosity, and authentic experiences. Using a five-point Likert scale, three motivational factors were identified: Sustainable Escape, Rural Immersion, and Authentic Stay. Results indicate that visitors increasingly value eco-friendly practices, local gastronomy, agritourism, and culturally rooted accommodations. These findings highlight how authentic, community centered experiences not only support local economies but also nurture entrepreneurship and environmental stewardship. The Terlan model demonstrates a practical pathway for rural destinations, such as Fruška Gora, to enhance competitiveness by integrating sustainability with cultural authenticity, thereby offering high-quality rural tourism experiences aligned with contemporary tourist expectations.